2010
DOI: 10.1088/0953-8984/22/30/305001
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of ideal and double layer reconstructions of ABO3(001) surfaces (A = Sr, Ba; B = Ti, Zr) from first principles

Abstract: We conducted a comparative study of various reconstructions for the (001) surfaces of SrTiO(3), BaTiO(3), SrZrO(3) and BaZrO(3) perovskites through calculations within the density functional theory. The atomic structure, the thermodynamic stability and the charge distribution of ideal AO or BO(2) terminations, as well as the so-called AO or BO(2) double layer reconstructions were analysed, and it was found that of all the BO(2) double layer reconstructions the most stable are the (2 × 2) and the (√2 × √2) ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 71 publications
(125 reference statements)
2
20
0
Order By: Relevance
“…These results are in good qualitative agreement with other Ab initio calculations dealing with ABO 3 (001) surfaces. [11][12][13][14][26][27][28][29][30] In addition, the shrinkage in the interlayer distance, Dd 1-2 , of the SnO 2 -terminated surface is larger than that of the BaO-terminated surface, which disagrees with what happens in the case of the (001) surface. Moreover, it is shown that the amplitude of the surface rumpling on the SnO 2 -terminated surface of 3.742% is slightly larger than that of 3.348% for the BaO-terminated surface, …”
Section: Basno 3 (001) Surface Relaxationsmentioning
confidence: 78%
See 2 more Smart Citations
“…These results are in good qualitative agreement with other Ab initio calculations dealing with ABO 3 (001) surfaces. [11][12][13][14][26][27][28][29][30] In addition, the shrinkage in the interlayer distance, Dd 1-2 , of the SnO 2 -terminated surface is larger than that of the BaO-terminated surface, which disagrees with what happens in the case of the (001) surface. Moreover, it is shown that the amplitude of the surface rumpling on the SnO 2 -terminated surface of 3.742% is slightly larger than that of 3.348% for the BaO-terminated surface, …”
Section: Basno 3 (001) Surface Relaxationsmentioning
confidence: 78%
“…9,10 Unlike the bulk materials, the surfaces of the materials exhibit completely different physical and chemical features. 11 Hence, it is essential to study the material surfaces and the linked physical and chemical properties in order to understand such phenomena occurring at the material surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest atomic relaxations of BaO-terminated and TiO 2 -terminated cubic BaTiO 3 (0 0 1) surfaces are on the first-layer atoms [11]. Iles et al [1] conducted a comparative study of various reconstructions for the (0 0 1) surfaces of SrTiO 3 , BaTiO 3 , SrZrO 3 and BaZrO 3 perovskites and showed that the largest atomic displacements for BO 2 terminated surfaces are in the first-layer oxygen atoms. This tendency is in correspondence with the present calculations of NbO 2 terminated KNbO 3 (0 0 1) surfaces.…”
Section: Knbo 3 (0 0 1) Surface Relaxationmentioning
confidence: 99%
“…In contrast to the bulk, thin films have larger surfaces. In addition, surfaces of ferroelectric materials are typically the first natural interface between a given material and the environment [1]. Therefore, it is particularly important to investigate the surface structure of ferroelectric thin films and the associated physical and chemistry properties affected by surfaces.…”
Section: Introductionmentioning
confidence: 99%